Analisis Pending Claim Badan Penyelenggara Jaminan Sosial (BPJS) Rawat Jalan pada Rumah Sakit XY di Wilayah Jawa Timur - Ais, Putri Lutfiah Rihadatul; Akhirruddin, Anita (MES Bogor, 2024)
This research aims to analyze the causes and impacts of pending claims for outpatient services under the Social Security Administering Body (BPJS) at XY Hospital in East Java. The study uses a descriptive approach with data collection through interviews with various parties involved in the claim process, including administration, collecting, complication, and finance departments. The results show that the main causes of delayed BPJS claims are incomplete documentation, coding errors, and issues in administrative verification. The impact of pending claims includes disruptions to the hospital's cash flow, hindering operational smoothness and patient care services. This research also provides recommendations for improvement, such as enhancing staff training, evaluating the claims system, and improving coordination between related departments to expedite and simplify the BPJS claim process.